2022
DOI: 10.3390/diagnostics12030600
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Radiofrequency as Therapy and Diagnostic Support in the Management of Musculoskeletal Pain: A Systematic Review and Meta-Analysis

Abstract: Radiofrequency (RF) is a minimally invasive procedure used to interrupt or alter nociceptive pathways for treating musculoskeletal pain. It seems a useful tool to relieve chronic pain syndromes, even if, to date, solid evidence is still needed about the effectiveness of this therapy. By this systematic review and meta-analysis, we aimed to evaluate the efficacy of RF in treating musculoskeletal pain. PubMed, Medline, Cochrane, and PEDro databases were searched to identify randomized controlled trials (RCTs) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 62 publications
0
8
0
1
Order By: Relevance
“…Many RCT studies, as displayed by Farì et al [17] in their meta-analysis, demonstrated that both pulsed or continuous or water-cooled RF (WCRF), could represent a promising therapy for treating chronic musculoskeletal pain, especially when other approaches are ineffective or not practicable. Their group also showed that continuous RF combined with therapeutic exercise in rehabilitating severe hip osteoarthritis is an attractive option for significant pain relief as it allows patients to carry out kinesitherapy more easily [18].…”
Section: Discussionmentioning
confidence: 99%
“…Many RCT studies, as displayed by Farì et al [17] in their meta-analysis, demonstrated that both pulsed or continuous or water-cooled RF (WCRF), could represent a promising therapy for treating chronic musculoskeletal pain, especially when other approaches are ineffective or not practicable. Their group also showed that continuous RF combined with therapeutic exercise in rehabilitating severe hip osteoarthritis is an attractive option for significant pain relief as it allows patients to carry out kinesitherapy more easily [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another minimally invasive technique used in the treatment of chronic musculoskeletal pain includes RFA also known as radiofrequency neurotomy (RFN). This nonsurgical procedure is used to treat chronic pain from an innervated structure typically of facet origin that ablates (disconnects) nociceptive pathways causing the pain (Farì et al, 2022; Huang et al, 2020; Wray et al, 2022). Ablation is typically done using high temperatures, cold temperatures, or chemicals.…”
Section: Physical Medicine and Rehabilitation Modalitiesmentioning
confidence: 99%
“…Both epidural steroid injections and RFAs give physiatrists additional means to treat back pain when more conservative options have failed. A systematic review and meta-analysis by Farì et al (2022) indicated RFA as a therapy favorable in treating chronic musculoskeletal pain when other methods are not feasible. Evidence-based guidance for the use of RFN identified by The American Society of Pain and Neuroscience examined a variety of anatomic uses of RFA resulting in practice guidelines (Lee et al, 2021).…”
Section: Physical Medicine and Rehabilitation Modalitiesmentioning
confidence: 99%
“…Широко используются диагностические блокады с местными анестетиками у тех пациентов, у которых Терапия боли нет эффекта от консервативной терапии. В таких случаях если введение анестетиков в область ФС или КПС приводит к исчезновению или существенному снижению боли (на 50% и более), выполняется введение анестетиков и кортикостероидов в область ФС и КПС [13,14], а также микрохирургические методы денервации, преимущественно радиочастотная денервация [22]. Эти методы терапии обычно уменьшают боль и улучшают функциональное состояние пациента, однако нет убедительных доказательств, что они имеют преимущество перед рекомендуемой экспертами тактикой, включаю щей применение нестероидных противовоспалительных средств (НПВС), кинезитерапию, психологические и другие консервативные методы лечения [19,21].…”
Section: целесообразно ли выявление анатомической причины хронической...unclassified